Regulatory issues of information flow in a virtual environment the internet in the context of providing of informational state sovereignty - Zadereyko, A. V.; Задерейко, А. В. (Одеса : Фенікс, 2014)
Nevertheless, we must always remember that the control and regulation of the flow of information from the state society can be interpreted not as an instrument of domination of the information interests of the state, and as the setting of information censorship. In this case, whatever the level of declared freedom of speech in the country, considered regulatory trends information flows in the virtual environment of the Internet, there are embedded in the legislative base states. In these processes, of course, there are positive and negative sides.
Zadereyko A. V. Regulatory issues of information flow in a virtual environment the internet in the context of providing of informational state sovereignty / A. V. Zadereyko // Правове життя сучасної України: матеріали Міжнар. наук. конф. проф.-викл. та аспірант. складу / відп. за вип. В. М. Дрьомін; НУ ОЮА, Півд. регіон. центр НАПрН України. – Одеса: Фенікс, 2014. – Т. 2. – С. 570-571.
Keywords: regulatory issues of information flow in a virtual environment the internet in the context of providing of informational state sovereignty; вопросы регулирования информационных потоков в виртуальном среда интернет в контексте обеспечения информационного суверенитета государства; питання регулювання інформаційних потоків в віртуальному осередку інтернет в контексті інформаційного суверенітету держави